2013
DOI: 10.1002/jbio.201200210
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive cross‐sectional imaging of proximal caries using swept‐source optical coherence tomography (SS‐OCT) in vivo

Abstract: The aim of this study was to determine the diagnostic accuracy of swept-source optical coherent tomography (SS-OCT) in detecting and estimating the depth of proximal caries in posterior teeth in vivo. SS-OCT images and bitewing radiographs were obtained from 86 proximal surfaces of 53 patients. Six examiners scored the locations according to a caries lesion depth scale (0-4) using SS-OCT and the radiographs. The results were compared with clinical observations obtained after the treatment. SS-OCT could detect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
86
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(92 citation statements)
references
References 23 publications
4
86
1
1
Order By: Relevance
“…In vitro studies showed an adequate to strong agreement, when SS-or SD-OCT were compared to histology [29,42,43], confocal microscopy, X-ray microtomography, or transverse microradiography and a diagnostic superiority compared to bitewing radiography [44] (Figures 1, 2, 5-11 and 14). In vitro studies showed an adequate to strong agreement, when SS-or SD-OCT were compared to histology [29,42,43], confocal microscopy, X-ray microtomography, or transverse microradiography and a diagnostic superiority compared to bitewing radiography [44] (Figures 1, 2 and 5-11 and 14). Image contrast and the spatial separation of the lesion body versus sound enamel can be further enhanced using polarization-sensitive OCT [45].…”
Section: Caries Diagnosismentioning
confidence: 94%
“…In vitro studies showed an adequate to strong agreement, when SS-or SD-OCT were compared to histology [29,42,43], confocal microscopy, X-ray microtomography, or transverse microradiography and a diagnostic superiority compared to bitewing radiography [44] (Figures 1, 2, 5-11 and 14). In vitro studies showed an adequate to strong agreement, when SS-or SD-OCT were compared to histology [29,42,43], confocal microscopy, X-ray microtomography, or transverse microradiography and a diagnostic superiority compared to bitewing radiography [44] (Figures 1, 2 and 5-11 and 14). Image contrast and the spatial separation of the lesion body versus sound enamel can be further enhanced using polarization-sensitive OCT [45].…”
Section: Caries Diagnosismentioning
confidence: 94%
“…It is a promising imaging modality, which does not require cutting and processing of the specimens and allows the visualization of microstructures of tissues and biomaterials in real time 24) . Recently, clinical OCT systems equipped with hand-held probes and suitable for intra-oral imaging have been launched by some manufacturers on a trial basis and showed a potential as a detecting tool for occlusal, interproximal and secondary caries, demineralization around orthodontic brackets as well as evaluation of dental materials defects [25][26][27][28] . The introduction of faster spectral domain systems 25) and incorporation of micro mechanical electrical systems into the probe designs 26) have facilitated three-dimensional imaging and adoption of OCT in clinical dentistry 29) .…”
Section: Optical Coherence Tomography For Evaluation Of Enamel and Prmentioning
confidence: 99%
“…Recently, clinical OCT systems equipped with hand-held probes and suitable for intra-oral imaging have been launched by some manufacturers on a trial basis and showed a potential as a detecting tool for occlusal, interproximal and secondary caries, demineralization around orthodontic brackets as well as evaluation of dental materials defects [25][26][27][28] . The introduction of faster spectral domain systems 25) and incorporation of micro mechanical electrical systems into the probe designs 26) have facilitated three-dimensional imaging and adoption of OCT in clinical dentistry 29) . Previous studies showed that OCT imaging of sealants enabled clear detection of voids and failures in the adaptation of materials 30,31) .…”
Section: Optical Coherence Tomography For Evaluation Of Enamel and Prmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, clinical OCT systems are under development based on the conventional SS-OCT technology. Shimada et al 16) demonstrated the diagnostic accuracy of SS-OCT in detecting and estimating the depth of proximal caries in posterior teeth in vivo. In their study, SS-OCT images and bitewing radiographs were evaluated by six dentists and results were compared with clinical observation obtained after the clinical treatment.…”
Section: Introductionmentioning
confidence: 99%